Questionnaires assessing the use of complementary health approaches in pediatrics and their measurement properties: A systematic review. (September 2020) - Alqudimat, Mohammad R.; Toupin April, Karine; Hundert, Amos; Jibb, Lindsay; Victor, Charles; Nathan, Paul C.; Stinson, Jennifer
Highlights: The use of Complementary Health Approaches (CHA) is common among pediatrics, particularly in children with chronic conditions. The use of some types of CHA may pose a potential risk of interactions when used in conjunction with conventional cancer treatments. To date, there is a lack of a thoroughly validated CHA questionnaire in pediatrics that can be used for research and in clinical practice. We identified two CHA questionnaires to hold promise that could be adapted for further reliability and validity testing. Abstract: Objectives: To identify questionnaires assessing the use of complementary health approaches (CHA) in pediatrics, describe their content, and appraise the methodological quality of the studies and the measurement properties of the questionnaires. Method: Major electronic databases were searched from 2011 to 2020. Studies which aimed to assess the use of CHA and studies which reported developing and validating CHA questionnaires in pediatrics were included. Two reviewers independently screened the studies, extracted the data, and rated the methodological quality of the studies and measurement properties of the questionnaires using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist. When consensus was not reached, a third reviewer was consulted. Results: Thirty-eight studies were included. From these studies, 35 CHA questionnaires with a variety of different items were identified. Only two studies aimed to evaluate the measurement properties of two questionnaires. One questionnaire, available as a self- and proxy-report, was initially validated in children with juvenile idiopathic arthritis, and the other, available as an interviewer-administered questionnaire, was validated in children with cancer. According to the COSMIN, the methodological quality of both studies was inadequate or doubtful, and both questionnaires was not thoroughly validated. Conclusion: This systematic review showed a lack of a thoroughly validated CHA questionnaire in pediatrics. However, two questionnaires were found to hold promise. To address this gap, one of the existing questionnaires should be adapted and further validated.